Integrating Artificial Intelligence into Makassar Oral Literature Learning to Support Cultural Sustainability - Abd. Rahim; Nursalam Nursalam; Kasma F. Amin; Andi Fatimah Yunus; Fadhl Mohammed Awadh Gharamah; Nurhikmah Nurhikmah (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
Makassar oral literature faces serious challenges in the digital era due to globalisation, the dominance of popular culture, and the declining interest of younger generations in local languages and traditions. This condition highlights the need for learning innovation that is oriented not only toward preservation but also toward cultural revitalisation through approaches relevant to technological development. This study aims to formulate a redesign of local literature learning based on artificial intelligence as a strategy to strengthen local cultural literacy and support the sustainability of Makassar’s intangible cultural heritage. The study employs a qualitative method with a descriptive-analytical approach. Data were collected through literature review, learning model development, and classroom observations involving students enrolled in an oral literature course in the Department of Regional Literature at Universitas Negeri Makassar. The participants were selected purposively based on their involvement in oral literature learning and their exposure to educational technology. Observations focused on students’ learning practices, their use of digital tools, and the pedagogical challenges encountered in learning Makassar oral literature. The data were analyzed through qualitative descriptive procedures, including data reduction, thematic categorization, interpretation, and the formulation of a proposed learning model. The results of the analysis led to the development of the AI-Enhanced Cultural Immersion model, which positions artificial intelligence as a pedagogical support system rather than as a substitute for cultural transmission. In this model, generative artificial intelligence is proposed to support the visual reconstruction of literary narratives, while natural language processing is used to facilitate dialogic and interactive engagement with oral traditions. Since this study does not involve empirical implementation or experimental testing of the model, the findings are presented as a conceptual and pedagogical proposal. The study concludes that the integration of artificial intelligence has the potential to support local cultural literacy and contribute to the revitalisation of Makassar oral literature in the digital era.